Improving by sustainability in sport facilities - Lucas, Susana (2013)
Sporting structures particularly in Portugal, which were built for Euro 2004, in addition to belonging to clubs, the rest, have a very low utilization rate. But all in general have high operating costs and little control in the use of resources available. From the cases of stadiums Letzigrund, Zurich, Switzerland and Amsterdam Arena, the Netherlands, there may be a new vision for the improvement of Portuguese stadiums. In the case of the stadium was the Letzigrund stadium in its construction was dubbed the Green Stadium, built for Euro 2008. Among the recommended measures were implemented immediately: Green roof: with a photovoltaic system with an area of 2500 m2 and Solar Thermal Collectors 90 m2, heating by pellets; Promoting green transport: public transport; Waste management by implementing reusable cup; Lighting System: Minergie. The Amsterdam Arena, even having been built in 1998, has now the objective for 2015, be the first zero carbon stadium. The Amsterdam ArenA strives: to be a platform for sustainable innovations; to reduce our own environmental impact, and that of our events; to be a good neighbor and a positive boost for the economy; to increase our sustainable impact together with others. It presents an analysis of the measures advocated by these two football stadiums for sustainability, and measures can be defined and advocated an example and be applicable in Euro 2004 stadiums. It is considered that the implementation of measures for sustainability in sports facilities can be made throughout his life in order to have lower cost and operating efficiency.